(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
William Somerset Maugham portraits an awesome family picture in ‘The Kite’. In this short story the interesting matter is the relationship among family members. A simple story exposes the complexities of human psychology in a lucid and catchy way. In remote past Maugham scattered the seed of separation which brings the theme of divorce in our modern loveless society. N ow divorce is every classes’ cup of tea in our society. Smashing the kite indicates smashing the lovely conjugal relationship in our modern society. This paper attempts to entrap the word picture of modern society in the short story ‘The Kite’ which was written in 1947.